The Alte Schäfflerei at Benediktbeuern Monastery – Conjunction of Architectural Conservation and Energy Performance Improvement in a Historic Buildings. Issue 1 (October 2021) - Kilian, R; Bichlmair, S; Krus, M; Merktle, D; Milch, C; Sedlbauer, K P
Abstract: This paper gives an introduction into the research and measures of monument conservation and energy performance improvement of the Alte Schäfflerei (Old Cooperage) in the monastery of Benediktbeuern in upper Bavaria, Germany. The works started in 2010 when a contract was made between the Monastery and the Fraunhofer Gesellschaft to establish the "Fraunhofer Centre for Conservation and Energy Performance of Historic Buildings". Both, resource and energy efficiency are approaches that are in the focus of the research. Moreover, all measures should comply with monument preservation rules and respect the original substance. The calculation of the impact of different energy saving measures like the improvement of the historic windows, internal and external wall insulation, attic and floor insulation as well as the use of renewable energies from the central power station of the monastery on the overall energy demand is presented.